First Record of the Turtle Barnacle Stephanolepas muricata from the Paciic Coast of Costa Rica - Corrales Gómez, Natalia (2012)
The sessile barnacles (Balanomorpha) included in the family Platylepadidae are obligatory symbionts of motile marine animals, with some species occurring solely on turtles, sea snakes, and ish (Newman & Ross 1976; Pfaller et al. 2012). Platylepadid barnacles occur partially to fully embedded within the host’s tissues - producing external wall elaborations that serve to anchor the barnacle (Badillo 2007; Ross & Frick 2007; Zardus & Balazs 2007). Stomatolepadine barnacles like Stephanolepas are characterized by nearly- to fully-encapsulating the shell in host tissue (Ross & Frick 2011). The shell of S. muricata is fragile and has a series of sutural elaborations that radiate outwards so as to cross-anchor the animal deep within the dermis of the host tissue (Fig. 1) (Frick et al. 2011).